A Mechanistic Study on the Fluidization and Enhancement Effects of Cineole Toward Stratum Corneum Intercellular Lamellar Lipids: A Liquid Crystalline Model Approach - Karami, Leila; Moghimi, Hamid Reza (Iranian journal of pharmaceutical research : IJPR, 2023)
Background: The stratum corneum (SC) serves as the primary barrier for permeation in human skin. Penetration enhancers, such as 1,8-cineole, are utilized to enhance the permeation of drugs. Cineole increases the permeation of chemicals through different mechanisms. However, its mechanism, particularly at high concentrations, has not been well-studied and is the subject of the present investigation. Objectives: In continuation of our previous studies, the present investigation aims to elucidate the mechanism of action and concentration dependency of the effects of 1,8-cineole on the structure, diffusional properties, and partitioning behavior of the SC at high concentrations. This will be achieved through lamellar liquid crystalline models and ex-vivo skin studies. Methods: A lamellar liquid crystalline lipid matrix model in the presence (25 - 90%, w/w) and absence of cineole was prepared from SC lipids and characterized by X-ray diffraction, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and polarized light microscopy (PLM) studies. Release of the model lipophilic drug (diazepam) from cineole and cineole-treated matrices and the permeation of the drug from cineole and cineole-containing matrices (as a vehicle similar to the stratum corneum lipids) through excised rat skin were studied. Drug assay was performed by HPLC. Results: The PLM, DSC, and X-ray studies showed that the model matrix had a lamellar gel-liquid crystalline structure, and cineole fluidized the structure concentration-dependently and created other mesomorphic textures, such as myelinic figures. Release experiments showed that diffusion coefficients remained almost constant at high cineole concentrations of 40-90%, suggesting similar fluidization states. Skin permeation studies indicated that the diffusion coefficient (estimated from lag-time) increased concentration-dependently and played a role in permeability coefficient (Kp) increments alongside the increased partitioning of the model drug into the skin. Data suggest that high concentrations of cineole at the skin surface might not provide enough cineole in the skin for full fluidization, despite the similarity of the vehicle to SC lipids and even at high concentrations. Conclusions: The enhancement effect of cineole is concentration-dependent and might reach maximum fluidization at certain concentrations, but this maximum might not be easily achievable when cineole is used in formulations as pure or in a vehicle.